2023
DOI: 10.1002/advs.202302701
|View full text |Cite
|
Sign up to set email alerts
|

Scalable, Patternable Glass‐Infiltrated Ceramic Radiative Coolers for Energy‐Saving Architectural Applications

Abstract: A huge concern on global climate/energy crises has triggered intense development of radiative coolers (RCs), which are promising green‐cooling technologies. The continuous efforts on RCs have fast‐tracked notable energy‐savings by minimizing solar absorption and maximizing thermal emission. Recently, in addition to spectral optimization, ceramic‐based thermally insulative RCs are reported to improve thermoregulation by suppressing heat gain from the surroundings. However, a high temperature co‐firing process o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 45 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…Thus, recently, two main strategies have been reported to promote the solar reflectance. One is to prepare polymer particle composite materials containing micro-nano fillers with a high refractive index such as Al 2 O 3 , 11–13 TiO 2 , 14–16 ZnO, 17,18 ZrO 2 , 19 and Y 2 O 3 . 7 Mandal et al 20 demonstrated that adopting Al 2 O 3 and BaSO 4 to construct a randomly distributed particle structure could significantly enhance the solar reflectance.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, recently, two main strategies have been reported to promote the solar reflectance. One is to prepare polymer particle composite materials containing micro-nano fillers with a high refractive index such as Al 2 O 3 , 11–13 TiO 2 , 14–16 ZnO, 17,18 ZrO 2 , 19 and Y 2 O 3 . 7 Mandal et al 20 demonstrated that adopting Al 2 O 3 and BaSO 4 to construct a randomly distributed particle structure could significantly enhance the solar reflectance.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advantages of particle-based structures, they encounter significant challenges in practical applications [38]. The primary issues include the difficulty of achieving uniform dispersion of microparticles in a highly viscous medium, the risk of cracking caused by thermal shrinkage and expansion, and the use of toxic materials in the fabrication process [39,40]. When PMMA is employed as a medium for a particle-based structure, it poses challenges in terms of sustaining its performance for a long time on the exterior walls of buildings or vehicles due to its thermoplastic nature.…”
Section: Introductionmentioning
confidence: 99%
“…The trade-off between the optical properties and applicability has always posed a challenge for practical implementation of PRC technology in the real world. Recently, PRC designs using pure inorganic materials to achieve reliable stability offer insight for addressing this challenge ( 40 42 ). In this work, we designed a hierarchically porous PRC material in the form of a bulk ceramic, which can be easily obtained using accessible inorganic materials through facile fabrication processes.…”
mentioning
confidence: 99%